Evidence of the 1950 Great Assam Earthquake Surface Break Along the Mishmi Thrust at Namche Barwa Himalayan Syntaxis. Issue 11 (8th June 2021) - Singh, Ishwar; Pandey, Arjun; Mishra, Rajeeb Lochan; Priyanka, Rao Singh; Brice, Atul; Jayangondaperumal, R.; Srivastava, Vaibhav
Abstract: Paleoseismological trenching at Kamlang Nagar along the Mishmi Thrust in the Eastern Himalayan Syntaxis, aided by radiocarbon analyses of charcoals yielding ages of 1111–914 B.C. to A.D. 1761–1968 infer primary evidences of co‐seismic surface faulting. Correlation with results of an earlier paleoseismological study indicates two successive surface rupturing earthquakes at ∼1800‐years interval, the most recent event very likely corresponding to the 1950 Assam earthquake ( M w 8.6). A dip‐slip displacement of 24.6 ± 4.6 m was estimated along a 25 ± 5°E dipping fault during the 1950 earthquake. Our study suggests dual surface faulting by the 1950 event along two orthogonal fault systems, that is, the Himalayan Frontal Thrust and the Mishmi Thrust. It thus emphasizes that, the seismicity pattern in the Mishmi Range where the locked zone of the Main Himalayan Thrust extends beyond the suture zone, is unlike that of the western and central Himalaya. Plain Language Summary: We use paleoseismological trenching and charcoal ages ranging 1111–914 B.C. and A.D. 1761–1968 to report the evidence of surface break by the 1950 great Assam‐Tibet earthquake ( M w 8.6) in the Eastern Himalayan Syntaxis. Geological observations and correlation with results from the adjoining trench site suggest two successive surface rupturing earthquakes at an interval of 1800 years in the Mishmi Range. Key Points: We provide the first evidence of surface rupture by the 1950 great Assam earthquake from the Mishmi Thrust in the eastern syntaxis We suggest a dual rupture style for the 1950 earthquake along the Himalayan Frontal Thrust and Mishmi Thrust A slip deficit of ∼1.4 m since 1950 is capable to generate an earthquake of M w ∼ 7.7 along the Mishmi Thrust in the present day